Vagueness and uncertainty - Bacon, A; Andrew Bacon (2012)
In this thesis I investigate the behaviour of uncertainty about vague matters. It is a fairly common view that vagueness involves uncertainty of some sort. However there are many fundamental questions about this kind of uncertainty that are left open, questions I shall attempt to answer in this thesis. Could you be genuinely uncertain about p when there is no matter of fact whether p? Could you remain uncertain in a vague proposition, even if you knew exactly which possible world obtained? Should your degrees of belief be probabilistically coherent? Should your beliefs in the vague be fixed by your beliefs in the precise? Could one in principle tell what credences a person has in the vague? This thesis defends the view that typically one ought to be genuinely uncertain about matters one considers to be vague; uncertainty about vague matters is no different in this regard from uncertainty about the future, the deep sea or far away galaxies.